Plantas de cobertura do solo e videiras: toxidez, fitorremediação e mecanismos de tolerância ao excesso de cobre - De Conti, Lessandro (2018)
The application of copper fungicides for the management of foliar diseases in grapevines (Vitis vinifera) increases copper (Cu) content in vineyard soils. This has been diagnosed in several traditional grape growing regions of the world. However, soil contamination with Cu is more significant in regions with acidic soils and high rainfall rates, which combined with elevated temperatures during the production cycle, increase the severity of diseases and consequently the use of chemical control. Such is the case in the southern region of Brazil. Cu accumulation in soil can reach toxic levels to grapevines and cover crops cohabiting the vineyards. It is more intense in regions that have sandy soils with low organic matter content, such as those found in the Campanha Gaúcha region of the state of Rio Grande do Sul (RS). These characteristics of the soils attribute low sorption capacity of Cu, promoting increased Cu levels in available forms, which increases the risk of phytotoxicity. The expansion of viticulture in the Campanha Gaúcha region occurred on native grasslands of the Pampa Biome. Therefore, the native species of the Biome spontaneously cohabit the vineyards of this region and are managed as cover crops, by mowing. In the winter period, hibernal species such as black oat (Avena strigosa) and perennial ryegrass (Lolium perene) are commonly introduced between the rows of grapevines. These plants may exude chelating substances that reduce Cu bioavailability and thus toxicity to grapevines. The study aimed to evaluate the effects of excess Cu on growth, nutritional status and root morphology in young grapevines and cover crops, the tolerance mechanisms triggered by plants in response to excess Cu, and the potential use of cover crops in the phytoremediation of Cu-contaminated vineyard soils. Five studies were carried out under controlled conditions using samples of an Typic Hapludalf Soil of a native grassland of the Campanha Gaúcha region for studies II, III, IV and V. Study I was done in nutrient solution. After the correction of pH and addition of macronutrients to the soil, three levels of Cu contamination were created by adding 0, 40 and 80 mg Cu kg-1. In study I, Cu levels were 0.2; 5; 25 and 50 μM Cu L-1. Plant growth parameters were evaluated in all the studies. Nutrient contents and root morphology were also evaluated in studies I, II, III and IV. Low molecular weight organic acids were determined in study I. Grapevine gas exchange and growth rate were determined in study V. High levels of Cu reduced the growth of young grapevines and cover crops, both those native to the Pampa Biome as well as introduced species. Excessive uptake of Cu reduced the efficiency of photosynthesis and triggered morphological changes in the root system, which reduced the volume of soil explored by roots and contributed to nutritional imbalances. Plants grown under Cu toxicity expressed tolerance mechanisms, which consisted in increased pH and exuding organic ligands, increasing Cu+2 complexation in the soil solution. The intercropping of native species promoted the growth of young grapevines at low and moderate levels of Cu contamination. The native plants of the Pampa Biome exhibit great potential for the phytoremediation of Cu-contaminated vineyard soils, because of their spontaneous occurrence and adaptability to local conditions.